2020
DOI: 10.1021/acs.langmuir.0c01360
|View full text |Cite
|
Sign up to set email alerts
|

Open-Channel Capillary Trees and Capillary Pumping

Abstract: Velocity of capillary flow in closed or open channels decreases as the flow proceeds down the length of the channel, varying as the inverse of the square root of time or as the inverse of travel distance. In order to increase the flow rate-and extend the duration of the flow-capillary pumps have been designed by mimicking the pumping principle of paper or cotton fibers. These designs provide a larger volume available for the wicking of the liquids.In microsystems for biotechnology, different designs have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…17 The average wall friction length of the root channel is estimated to be 259 µm from our 𝜆~ preceding work. 15,18 It was shown that the average friction length produces the value of the average wall friction by the formula . 12 𝜏 = 𝜇 * 𝑉/𝜆 The channels were designed using computer aided design (CAD) software (Solidworks 2017, Waltham, MA) and the design files were converted to G-code using computer aided manufacturing (CAM) software (Fusion 360).…”
Section: Fabrication Of Capillary Tree Channelsmentioning
confidence: 99%
See 2 more Smart Citations
“…17 The average wall friction length of the root channel is estimated to be 259 µm from our 𝜆~ preceding work. 15,18 It was shown that the average friction length produces the value of the average wall friction by the formula . 12 𝜏 = 𝜇 * 𝑉/𝜆 The channels were designed using computer aided design (CAD) software (Solidworks 2017, Waltham, MA) and the design files were converted to G-code using computer aided manufacturing (CAM) software (Fusion 360).…”
Section: Fabrication Of Capillary Tree Channelsmentioning
confidence: 99%
“…This motion has already been analyzed in our prior work. 15 Let us recall that the marching distance in the open root channel (the channel before the beginning of the bifurcations) is given by ( 1)…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, SCF can be observed in open microfluidic or mesofluidic channels where at least one side of the channel is open to the air. [12][13][14][15][16][17] Unlike conventional droplet microfluidics, our system has one side of the channel exposed, literally removing the ceiling to create an open air-liquid interface. The open surface of the channel gives access to the channel that conventional droplet microfluidics with closed, walled off channels does not provide; for example, a researcher can directly pipette into the channel or add/retrieve droplets, solid objects such as magnetic beads, or tissue samples.…”
Section: Introductionmentioning
confidence: 99%
“…(1, 2, [5][6][7][8][9][10][11] In our system, we autonomously generate droplets in an open channel without pumps or tubing by leveraging the inherent hydrostatic pressure difference between two immiscible fluids (the fluorinated carrier phase and aqueous phase), capillary pressure, and spontaneous capillary flow (SCF) -flow induced by capillary action. (12)(13)(14)(15)(16)(17) In our autonomous droplet generating system, the top side of the channel is exposed to air, rather than being enclosed by a ceiling, which gives access to the channel where conventional droplet microfluidics with enclosed channels does not. Open channels are advantageous because a researcher can directly pipette into the channel or add/retrieve droplets, solid objects such as magnetic beads, or tissue samples as they wish.…”
Section: Introductionmentioning
confidence: 99%